Isolation and Characterization of Avirulence Genes in Magnaporthe oryzae - Jee, Mui Sie; Whye Kit Lim, Leonard; Azelin Dirum, Martina; Che Hashim, Sara Ilia; Masri, Muhammad Shafiq; Ying Tan, Hui; San Lai, Lee; San Yeo, Freddy Kuok; Hui Chung, Hung (Borneo Journal of Resource Science and Technology, 2017)
Magnaporthe oryzae is a fungal pathogen contributing to rice blast diseases globally via their Avr (avirulence) gene. Although the occurrence of M. oryzae has been reported in Sarawak since several decades ago, however, none has focused specifically on Avr genes, which confer resistance against pathogen associated molecular pattern-triggered immunity (PTI) in host. The objective of this study is to isolate Avr genes from M. oryzae 7’ (a Sarawak isolate) that may contribute to susceptibility of rice towards diseases. In this study, AvrPiz-t, AVR-Pik, Avr-Pi54, and AVR-Pita1 genes were isolated via PCR and cloning approaches. The genes were then compared with set of similar genes from related isolates derived from NCBI. Results revealed that all eight Avr genes (including four other global isolates) shared similar N-myristoylation site and a novel motif. 3D modeling revealed similar β-sandwich structure in AvrPiz-t and AVR-Pik despite sequence dissimilarities. In conclusion, it is confirmed of the presence of these genes in the Sarawak (M. oryzae) isolate. This study implies that Sarawak isolate may confer similar avirulence properties as their counterparts worldwide. Further R/Avr gene-for-gene relationship studies may aid in strategic control of rice blast diseases in future.